Measurement of Corner-Mode Coupling in Acoustic Higher-Order Topological Insulators - Li, Xiao; Wu, Shiqiao; Zhang, Guanqing; Cai, Wanzhu; Ng, Jack; Ma, Guancong (Frontiers in Physics, 2021)
Recent developments of band topology have revealed a variety of higher-order topological insulators (HOTIs). These HOTIs are characterized by a variety of different topological invariants, making them different at a fundamental level. However, despite such differences, the fact that they all sustain higher-order topological boundary modes poses a challenge to phenomenologically tell them apart. In this work, we present experimental measurements of the coupling effects of topological corner modes (TCMs) existing in two different types of two-dimensional acoustic HOTIs. Although both HOTIs have a similar four-site square lattice, the difference in magnetic flux per unit cell dictates that they belong to different types of topologically nontrivial phases – one lattice possesses quantized dipole moments but the other is characterized by quantized quadrupole moment. A link between the topological invariants and the response line shape of the coupled TCMs is theoretically established and experimentally confirmed. Our results offer a pathway to experimentally distinguish HOTIs.